The Role of Acupuncture in Cancer Care: From Symptom Alleviation to Tumor Suppression: A Narrative Review - Setiawan, Natasha; Mihardja, Hasan (Indonesian Journal of Cancer, 2024)
Background: Cancer remains a prevalent disease worldwide, a leading cause of mortality worldwide. Cancer presents numerous treatment challenges, from determining the efficacy of treatment modalities to managing a wide array of therapy-related side effects. Acupuncture, a traditional form of therapy, is increasingly being recognized for its potential in alleviating cancerrelated symptoms and treatment side effects. Acupuncture functions by targeting specific points in the body, leading to the modulation of neurotransmitters within the central nervous system. Research has shown that acupuncture can alleviate cancer-related symptoms that range from chemotherapy-induced nausea and vomiting, pain, and several other side effects. This mechanism has been linked to the reduction of inflammation and alleviation of pain, proving beneficial to cancer patients. Its effectiveness varies across different types of cancers. As cancer research continues to grow, so does the research on genetic role in cancer.  Methods: This narrative review assessed the influence of acupuncture on gene expression regulation in cancer. We searched three databases and found eight studies indicating that acupuncture plays a role in cancer management through the regulation of gene expression.  Results: Studies have suggested acupuncture’s potential in reducing tumor growth in different types of cancer, such as osteosarcoma, breast cancer, and colorectal cancer, possibly through mechanisms involving gene regulation and inflammatory cytokines.  Conclusions: While genetic factors can influence individual responses to acupuncture, the therapy is generally considered safe and has been accepted by a significant percentage of cancer patients and caregivers.